2014
DOI: 10.5120/17809-8636
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian Cloud-Government between Implementation and Challenges

Abstract: Cloud computing is a modern style of advance and modernization in network environment which takes the advantage of a various wire and wirelss technologies as distributed, and parallel processing which oriented to service architecture. The E-government services are concerned about sharing existing resources. E-governments are available online and they have to adapt new technology that will enhance the service provided to their citizens. This paper focuses on cloud computing and e-government concepts and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Therefore, it can be stated that mobility, cost, backup and disaster recovery, scalability and flexibility are significant determinants for employee intentions to adopt cloud computing, as the extent to which employees believe that cloud computing could provide such benefits, this would influence their intentions positively to adopt, however, in contrary to expectation agility was identified as insignificant determinant for current sample, which is in contradict with result by SlaibiAlsharafat et al [43] and Joshi et. al [23].…”
Section: Fig 2 Path Testing and Significancecontrasting
confidence: 68%
See 1 more Smart Citation
“…Therefore, it can be stated that mobility, cost, backup and disaster recovery, scalability and flexibility are significant determinants for employee intentions to adopt cloud computing, as the extent to which employees believe that cloud computing could provide such benefits, this would influence their intentions positively to adopt, however, in contrary to expectation agility was identified as insignificant determinant for current sample, which is in contradict with result by SlaibiAlsharafat et al [43] and Joshi et. al [23].…”
Section: Fig 2 Path Testing and Significancecontrasting
confidence: 68%
“…In such a way, the agility of the cloud computing limits time wastage for accessing the allocation of the national resources. As a result, all the citizens will have ample access to real-time and updated services and resources [43]. The citizens need up-to-date services in a continuously flowing manner for effective participation.…”
Section: H2: Cost Has a Significant Positive Impact On Adoption Of Cl...mentioning
confidence: 99%
“…The platform will also enhance government entities' utilization of server hardware from the industry average of approximately 15% to more than 90%. Furthermore, by centralizing its operations through a unified data center the Government of Jordan will be able to ensure that its server power is maximized [10]. In light of the above developments, this study is both timely and relevant.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Liang et al [30] suggested a holistic approach by using grounded theory to examine determinants of e-government cloud adoption among government agencies in China. The studies that focused on middle east region, [49,50,51], explored CC benefits and challenges for e-government theoretically in Jordan and United Arab Emirates respectively. Other studies assessed CC adoption for e-government implementation in Yemen [40,52] and [37] investigated the factors affecting Saudi government to adopt CC.…”
Section: Previous Studiesmentioning
confidence: 99%